Incubation Strengthening Social Business Based on Javanese-Islamic Culture - Ronny Ersya Novianto; Ahmad Saifullah (Universitas Brawijaya, 2021)
This study aims to build a sustainable model for empowering Arjuno coffee farmers. This study uses a qualitative method. This study indicates that Arjuno coffee farmers adhere to Javanese-Islamic values and culture; this is the basis for describing Pre-Incubation Strengthening of Javanese-Islamic Culture-Based Social Business (ISBSBoJI). Meanwhile, ISBSBoJI was built by increasing the capability and productivity of Arjuno coffee farmers with market orientation and collaboration. The goal of Post-ISBSBoJI is to increase trust and sustainable welfare.